Visibility Framework and Performance Analysis for Free Space Optical Communications in Satellite Links - Javier Garcia Olmedo; Victor P. Gil Jimenez (IEEE Access, 2023)
This paper studies and provides a performance analysis for the atmospheric influence on the visibility in Free Space Optical Communications (FSOC). With a focus on ground station-satellite links, it aims to present and analyse the most commonly used attenuation models for the main atmospheric events, establish relationships and dependence never analyzed before, such as for example in the case of rain and snow. As the characterisation of atmospheric attenuation is far from following a pattern in different locations, this work is intended to simplify and unify all the atmospheric events, proposing the visibility as the main single parameter to compare and analyze them. This parameter is available in most of the measurements, including in the fog scenarios. Besides, the effects of clouds are also analyzed, establishing relationships to visibility, in the case of attenuation calculations, suggesting the use of certain attenuation models and providing a new technique for the calculation of the link blockage in the presence of clouds, which are reported by aviation codes in meteorological stations. Besides, all the sites accessed to obtain the meteorological parameters and tools used for the study in this paper are listed in section II.